Long noncoding RNA SNHG6 promotes oesophageal squamous cell carcinoma by downregulating the miR‐101‐3p/EZH2 pathway. Issue 2 (12th November 2021) - Zhang, Yueli; Li, Ruijia; Ding, Xiaoliang; He, Meng; Zhang, Rui
Abstract: Long noncoding RNAs (LncRNAs) have been reported to play a vital role in the development of oesophageal squamous cell carcinoma (OSCC). Our previous study revealed that the significant upregulation of the LncRNA small nucleolar RNA host gene 6 ( SNHG6 ) in OSCC promotes OSCC tumourigenesis. However, the mechanisms underlying the dynamics of SNHG6 expression in OSCC have rarely been studied. In this study, we verified the tumour‐promoting effect of SNHG6 through sponging miR‐101‐3p, and their levels were negatively correlated in human samples of OSCC. In addition, miR‐101‐3p overexpression reversed the effect of SNHG6 . Moreover, we confirmed that SNHG6 /miR‐101‐3p affects OSCC by regulating the expression of the enhancer of zeste 2 (EZH2). The effect of EZH2 silencing resembled closely that of SNHG6 knockdown. EZH2 silencing inhibited the expression of protein cyclin D1 and β‐catenin, but in contrast, it enhanced the expression of E‐cadherin. These findings demonstrated the oncogenic role of SNHG6, which promotes OSCC progression by regulating the expression of EZH2 through its interaction with miR‐101‐3p. These findings may help in improving the diagnosis and treatment methods of OSCC.